Post-Byzantine Period of Last Judgment Scenes in Trabzon Vazelon, Kaymaklı and Sümela Monasteries - A. Nazlı Soykan (Art-Sanat)
The territory of the Trabzon Greek Empire, founded in 1204, was inhabited by many different peoples for centuries. Construction activities also increased with the new political organisation in Trabzon in the 13th century. During this period, either new churches were built, or additions were made to existing structures. The fact that the region is sheltered and suitable for seclusion, the monasteries developed effectively. There are six known monasteries in Trabzon: Sümela Monastery, Vazelon Monastery, Kuştul Monastery, Kaymaklı Monastery, Girls (Panagia Theokephastros) Monastery and Girls (Panagia Keramesta) Monastery. While some of these six monasteries have survived to the present day in good condition, others are almost extinct. One of the standard features of the monasteries in Trabzon is the continuation of construction activities from the first day they were founded until the day they were abandoned, and another is the choice of themes in the wall paintings.The subject of the study is the Last Judgment scenes in the monasteries of Trabzon, which are dated back to the PostByzantine Period. As a result of the research conducted in this context, it was understood that this scene was depicted in Sümela, Kaymaklı and Vazelon Monasteries among the monasteries in Trabzon. In this study, the Last Judgement scenes in the three monasteries were analysed in detail, their drawings were made, and they were discussed comparatively with similar examples both in and outside the region.